Spatial and temporal distribution pattern of phosphorus fractions in a saline lowland river with agricultural land use (Salado River, Buenos Aires, Argentina) - Gabellone, Nestor Adrian (2013)
The main river of the Buenos Aires province, the Salado (length, 600 km; basin area, 150,000 km2), which drains one of the country's most extensive agricultural regions, is impacted by human activities (agriculture, hydraulic modifications), although the extent and mechanism of those impacts have yet to be clarified fully. This study investigated the temporal and spatial variations in concentrations of different phosphorus fractions in the Salado and its channels and tributaries to examine the potential influences of land use on the phosphorus dynamics in the basin. The data collected between 1997 and 1999 - during which period the basin experienced El Niño and La Niña events - indicated that the main phosphorus input occurred upstream and was mainly attributable to agricultural runoff. In support of this notion, the timing of the spring peak of total phosphorus concentrations (3,500 μg L-1) corresponded to the period of highest agricultural activities in a tributary of the headwaters. Of the total dissolved phosphorus, the particulate phosphorus and the dissolved reactive phosphorus were the main fractions in the headwaters. Data were also collected in the lower sector of the basin during the flooding periods between 2002 and 2003. These results revealed that a large total-phosphorus transport in the spring was related to a high discharge as a result of heavy rainfall. As with the results obtained in the entire basin, the particulate phosphorus fraction was primarily responsible for the increase in total phosphorus. We furthermore found that the phosphorus concentrations decreased near the mouth of the Salado, where extensive wetlands were present.